Community Economic Empowerment through Local Commodity Development: A Case Study of the Paradiso Farmer Group in Pati Regency - Muchammad Zamzam, Noor; Khoiriyah, Nur (Prodi Pengembangan Masyarakat Islam Fakultas Dakwah dan Ilmu Komunikasi UIN Mataram, 2025)
The Paradiso Farmer Group initiated the development of kopyor coconut as a local commodity, which serves as one of the leading agricultural products in Pati Regency. This research employs a field study approach with data collection methods including observation, interviews, and documentation. findings reveal that the empowerment process of the Paradiso Farmer Group consists of four main stages: planning, implementation, institutionalization, and monitoring-evaluation. The planning stage involves recognizing the potential of kopyor coconut, identifying market opportunities, and formulating the group’s vision, mission, and objectives. Finally, the monitoring and evaluation stage consists of conducting regular monthly meetings to gather feedback, address challenges, and accommodate suggestions for improvement. The improvement in economic empowerment is evident through indicators of enhanced economic welfare, reflected in the fulfillment of basic needs such as adequate clothing, food, housing, education, and healthcare.